RETRACTED Assessing Enterprise Resource Planning (ERP) Systems Customization in SMEs - Ramadhan, Sherzad; Koutaini, Hassan; Aridah, Ma’moun W.; Ahmed, Fareeba (European Scientific Journal, ESJ, 2019)
Enterprise Resources Planning (ERP) are information systems designed to manage all the processes of an organization so that they allow and facilitate decision-making from a global perspective of the organization as a whole, and not only from a departmental point of view. Therefore, this type of systems become a key factor in organizations. However, not all ERP issuitable for all organizations, and it is very important that each organization implement the ERP system that best suits their processes and characteristics, otherwise referred to as customization. For this, establishing and following a customization process is fundamental. There are different studies that try to identify and propose the most appropriate steps to follow for the correct customization of ERP systems, but most focus only on one part of the process, and are based on cases of multinationals or large companies which lack the unique ownership types, business processes, and stage of organizational growth characteristic of SMEs. For thisreason, they are not applicable to small and medium-sized enterprises (SMEs). Therefore, this article assesses the customization of ERP Systems with the focus on proposing a methodology for the customization of a customized ERP system (MCERP) suitable for an SME that can serve as a guide for these types of companies in the customization of an ERP system.